Upaya Memikat Kesetiaan Nasabah Melalui Kualitas Pelayanan Dan Promosi Kredit (Perumda BPR Bank Kulon Progo) - Emmanuelle, Misael Gaharu; sofiati, sofiati (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2025)
This study aims to analyze the influence of service quality and credit promotion on customer loyalty at Perumda BPR Bank Kulon Progo. Service quality and credit promotion are two key factors that can enhance customer satisfaction and loyalty in the banking sector. The research employs a quantitative approach with a simple random sampling technique, involving 150 customers of BPR Bank Kulon Progo. Data collection was conducted through questionnaires and analyzed using multiple linear regression tests The results indicate that service quality has a positive and significant impact on customer loyalty. Likewise, effective credit promotion also contributes significantly to increasing customer loyalty. Simultaneously, these two variables have a stronger impact on loyalty than their individual influences. Based on these findings, Perumda BPR Bank Kulon Progo is advised to continuously improve service quality by optimizing digital banking services and providing staff training to enhance responsiveness to customer needs. Additionally, credit promotion strategies should be more innovative and tailored to customer preferences to increase engagement and loyalty.